2021
DOI: 10.1038/s41409-021-01478-5
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation for patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN)

Abstract: Blastic Plasmacytoid Dendritic Cell Neoplasm (BPDCN) is an aggressive hematological malignancy; however, some patients achieve durable remission with allogeneic hematopoietic cell transplantation (allo-HCT). We report on all 17 patients with BPDCN who underwent allo-HCT at our center between 2000 and 2020. The median age was 39 (18-67) years. All (n=16, 94%), except one patient, had systemic disease involving bone marrow and/or other organs. Ten patients (59%) were in first complete remission (CR1) at allo-HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Sapienza et al [ 14 ] performed whole-exome sequencing and RNA sequencing on 14 BPDCN cases, identified deregulation of the epigenetic program as a genetic hallmark of BPDCN, and suggested a novel therapeutic approach based on the combination of two hypomethylating agents, 5′-azicytidine and decitabine. Stem cell transplantation has been shown to result in durable remissions [ 38 , 39 ]. Our studies also showed that stem cell transplantation significantly prolonged the overall survival of patients with BPDCN.…”
Section: Discussionmentioning
confidence: 99%
“…Sapienza et al [ 14 ] performed whole-exome sequencing and RNA sequencing on 14 BPDCN cases, identified deregulation of the epigenetic program as a genetic hallmark of BPDCN, and suggested a novel therapeutic approach based on the combination of two hypomethylating agents, 5′-azicytidine and decitabine. Stem cell transplantation has been shown to result in durable remissions [ 38 , 39 ]. Our studies also showed that stem cell transplantation significantly prolonged the overall survival of patients with BPDCN.…”
Section: Discussionmentioning
confidence: 99%
“…13 The ability to achieve sustained complete remission after HSCT is predicated on the ability of patients to withstand myeloablative treatment. 14 For some older patients, reduced-intensity conditioning using fludarabine-containing modalities or low-dose dexamethasone, VP16, ifosfamide, and carboplatin have been used for this reason before allo-transplantation. 15,16 Although induction chemotherapy followed by HSCT became widely adopted in the management of BPDCN and was shown to provide durable disease control in selected fit patients, the effect on disease-free survival was only marginal compared with the effect of chemotherapy alone.…”
Section: Conventional Chemotherapeutic Agentsmentioning
confidence: 99%
“…Among responders in each of the frontline treatment groups, a common significant variable was the ability to undergo HSCT, especially in CR1, which, regardless of frontline treatment regimen selected, remains a very important part of a curative approach in BPDCN, especially for younger/fit patients. 51 Despite no improvement in median OS compared with other treatment regimens, the ability to yield a higher CR rate with low rates of adverse events suggests that HCVAD retains an important role in the frontline treatment of BPDCN. As above, HCVAD represents the optimal combination of vinca alkaloid, glucocorticoid, anthracycline, and combination chemotherapy, in addition to intrathecal chemotherapy, as an intensive and efficacious frontline regimen for BPDCN.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to the heterogenous group of patients with varying degrees of disease involvement, and of subsequent lines of therapy. Among responders in each of the frontline treatment group, a common significant variable was the ability to undergo HSCT, especially in CR1, which, regardless of frontline treatment regimen selected, clearly remains a very important part of a curative approach in BPDCN, especially for younger/fit patients 51 . Despite no improvement in median OS compared to other treatment regimens, the ability to yield a higher rate of CR with low rates of adverse events suggests that HCVAD remains an important role in the frontline treatment of BPDCN.…”
Section: Discussionmentioning
confidence: 99%